Šauliai Nepriklausomybės kovose - Jurevičiūtė, Aušra; Veilentienė, Audronė (Lietuvos istorijos studijos, 1998)
The Riflemen Union (RU) of Lithuania was established on the initiative expressed by the Military Intelligence of the Ministry of National Defence and Lithuanian intelligentsia. The purpose of the organization was to consolidate society for a struggle against the enemies of Lithuania. During the war against the Bolsheviks, guerrilla detachments began to appear which, however, had to be united, armed, and employed expediently for the fight against the fighters of General Bermont-Avalov and the approaching soldiers of Poland. The RU of Lithuania became the uniting force of the fight detachments to banish the Bermont soldiers out of Lithuania. The Riflemen took the city of Šiauliai and kept it until their own forces had arrived. It was the most successful operation of RU. During the fights against the soldiers of Bermont, the Union performed according to guerrilla tactics. They were involved in around 100 armed conflicts. The fighters of Russian General Bermont-Avalov had not yet been banished when the Polish soldiers started robbing the local population on the Lithuania-Poland border. The newly created RU units performed the task of defending the local inhabitants. When the war broke out with Poland, RU established four field headquarters to coordinate RU activities at the front as well as in the rear. There were Riflemen from the small town of Perloja in the Union who distinguished themselves particularly in many actions by beating off the Polish attacks in various parts of South-East Lithuania. Unfortunately, in the tightest point of the struggle, disagreements between the Ministry of National Defence and RU emerged, which were adjusted by applying appropriate laws. Despite the denial of the need for RU and their patriotism expressed by most of the officers, the members of the constituent Seimas acknowledged the merits of RU in the struggle for independence. After the fights with Poles were finished, a neutral zone was appointed to be guarded exclusively by RU, led by officers—regional instructors. For their participation in the fights for independence, members of RU and volunteer creators of the Army were granted the privilege to acquire land on favorable terms.